Bali Cow Dung Management in Ayunan Village, Abiansemal Sub-District of Badung - Ni Made Ayu Gemuh Rasa Astiti; A.A.Rai Sita Laksmi; Gusti Agung Putu Eryani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Ayunan Village, located in the Abiansemal district of Badung, Bali. This village is about 20 km to the north from Denpasar city, towards the village of Sangeh tourist attraction and ayun park. Balinese cattle are germ plasm that must be preserved, because Bali is one of the sources of Balinese cattle breeding and the only area believed to have pure genetic B ali cattle. The increase in income will encourage farmers to raise more cattle, Balinese cattle rearing pattern is still traditional and only as a sideline in between farming time. The process of managing the maintenance of cows in partners has been good although it is still very simple. Direct observations in the Karang Ayu livestock group in Ayunan village, Abiansemal District, illustrated that Bali cattle rearing activities are very constrained by capital, feed, cow rearing management, manure channels and how to increase farmers' income from cow dung processing businesses. The main problems that will be the focus of solving the problem are the low productivity in processing manure into organic fertilizer and the low business efficiency and business sustainability of organic fertilizer products from manure. The methods used are: Presentation and plot as well as direct practice of making manure from cow dung using EM4 candy and fermented for 4 weeks. The results of this activity are expected to increase production and productivity and produce organic fertilizer from cow dung that can be sold so as to increase the income of Balinese cattle farmers in Ayunan Village.